A sequestered pool of aminoacyl-tRNA in mammalian cells. - Negrutskii, B S (1992)
We have recently proposed that aminoacyl-tRNA is channeled during protein synthesis in vivo--i.e., it is directly transferred among the components of the protein-synthesizing machinery and does not mix with aminoacyl-tRNA molecules introduced from outside the cell. To understand the structural basis for these functional properties, we have examined the disposition of aminoacyl-tRNA within the cell. To do this we have developed a Chinese hamster ovary (CHO) permeabilized-cell system using the plant glycoside saponin. We show, using a mixture of free 14C-labeled amino acids and 3H-labeled aminoacyl-tRNAs, that 14C-labeled aminoacyl-tRNAs synthesized endogenously from the free amino acids are preferentially sequestered within the cell, whereas their exogenous 3H counterparts distribute between the inside and outside of the cell based solely on the relative volumes of the two compartments. Furthermore, the endogenous 14C-labeled aminoacyl-tRNA population is resistant to pancreatic ribonuclease action, whereas the 3H molecules are rapidly degraded. We conclude, based on these observations, that aminoacyl-tRNAs synthesized in vivo are continually associated with components of the protein synthesis machinery and are thereby retained within the permeabilized cell and are also protected from RNase action. These data provide independent evidence for the channeling model of protein biosynthesis.